Changes in soil properties with long-term organic inputs due to distance from homestead and farm characteristics in southern Ethiopian farmlands - Yakob, G.; Habte, M.; Smith, J. U.; Hallett, P.D.; Phimister, E.; Rivington, M.; Black, H.; Mekuria, Wolde (Elsevier, 2023)
Traditional farming systems across much of Sub-Saharan Africa have greater organic inputs near to the homestead than in fields further away. This is likely to produce a fertility gradient that impacts production capacity, and so provides an opportunity to explore impacts of organic amendments on soils. Across 198 farm plots in 69 households in Halaba, Southern Ethiopia, we investigated the influence of different organic input systems on soil properties. The study also examined the influence of household and farm characteristics on the adoption of land management practices and its impact on soil properties. Samples were taken from farm plots located close (300 m) from the homestead, representing different levels of organic amendments. Soils located close to homesteads had significantly greater soil organic carbon, cation exchange capacity and soil nutrient content compared to soil located near and far from the homestead areas. Soil organic carbon concentrations close to the home were 15%, 27% and 45% greater than farm plots located at far from the home in Andegna Choroko, Asore and Lay Arisho kebeles, respectively. Across all sites, the mean soil organic carbon stock ranged from 20.6 t ha- 1 to 84.6 t ha- 1 , depending on the location of the plots with respect to the homestead. Household and farm characteristics also influenced land management practices and soil properties. In some catchments, farm plots managed by female headed households and relatively rich farmers displayed significantly greater soil organic carbon than farm plots managed by male headed and relatively poor households. This was likely due to greater organic inputs in female headed households in areas where men were otherwise engaged in off-farm activities and in wealthier households with greater access to organic manures. Tree cover in farmlands influenced accumulation of soil organic carbon. The results suggest that out-scaling farm management practices that are common around homesteads, such as adding animal manure or household wastes and maintaining tree cover, would help to improve key soil properties and agricultural productivity.